2021
DOI: 10.1038/s41467-021-20930-0
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies targeting a Mycobacterium transporter protein mediate protection against tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) exposure drives antibody responses, but whether patients with active tuberculosis elicit protective antibodies, and against which antigens, is still unclear. Here we generate monoclonal antibodies from memory B cells of one patient to investigate the B cell responses during active infection. The antibodies, members of four distinct B cell clones, are directed against the Mtb phosphate transporter subunit PstS1. Antibodies p4-36 and p4-163 reduce Mycobacterium bovis-BCG and Mtb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 48 publications
(69 reference statements)
0
45
0
Order By: Relevance
“…Antibody titers were assessed to five Mtb antigens that vary in composition, structure, function and localization: purified protein derivative (PPD), the total protein fraction from virulent mycobacterium 13 , lipoarabinomannan (LAM), a critical cell wall glycolipid 14 , HspX, a stress-induced intracellular protein 15 , and PstS1 and Apa, cell membrane-associated glycoproteins linked to host cell invasion 16 , 17 . Of note, antibodies specific to LAM, HspX and PstS1 ameliorate TB disease in mouse passive transfer studies 18 20 , and antibody responses to each of the five antigens have been observed during Mtb infection in humans 20 22 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Antibody titers were assessed to five Mtb antigens that vary in composition, structure, function and localization: purified protein derivative (PPD), the total protein fraction from virulent mycobacterium 13 , lipoarabinomannan (LAM), a critical cell wall glycolipid 14 , HspX, a stress-induced intracellular protein 15 , and PstS1 and Apa, cell membrane-associated glycoproteins linked to host cell invasion 16 , 17 . Of note, antibodies specific to LAM, HspX and PstS1 ameliorate TB disease in mouse passive transfer studies 18 20 , and antibody responses to each of the five antigens have been observed during Mtb infection in humans 20 22 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In a recent clinical trial of 2655 participants, authors reported that the use of bezlotoxumab (monoclonal antibody against C. difficile toxin) for treating C. difficile infection resulted in a lower recurrence of infection (Wilcox et al, 2017 ). In another recent study, Watson et al ( 2021 ) generated a monoclonal antibody from B cells of a patient to be used against Mycobacterium tuberculosis infection in mice. Monoclonal antibodies are costlier than producing antibiotics but have many benefits and more studies in this direction will help can help transform medicine.…”
Section: Antibiotic Alternatives and Use Of Probiotics For Restoring ...mentioning
confidence: 99%
“…The limitation of these studies is that they only focused on epitopes singly identified from CD4 + T lymphocytes [helper T lymphocytes (Th)] or CD8 + T lymphocytes (CTLs) rather than epitopes synchronously identified from Th cells, CTL cells, and B cells. Although the traditional view is that the host clearance and killing of M. tuberculosis mainly depend on CD4 + T lymphocytes and CD8 + T lymphocytes, accumulated data show that B lymphocytes also play an irreplaceable role in fighting against M. tuberculosis (Gong et al, 2018(Gong et al, , 2021Watson et al, 2021). Therefore, peptides binding to Th cells, CTL cells, and B cells should be considered when designing new candidate biomarkers based on epitopes for distinguishing LTBI from aTB and BCG-vaccinated HCs.…”
Section: Peptidesmentioning
confidence: 99%